2000
DOI: 10.1176/appi.ajp.157.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Nonpsychotic Patients in Community Clinics

Abstract: Most patients met the diagnostic criteria for conditions for which there are proven treatments; however, inaccurate diagnosis proved common. This barrier to optimal treatment could be ameliorated with the use of structured interviews for common diagnoses. Scores on social/interpersonal measures support the premise that DSM symptoms provide only part of the relevant information about patients' conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
0
8

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(202 citation statements)
references
References 27 publications
3
191
0
8
Order By: Relevance
“…Consistent with Shear et al (2000) and Taggart et al (2006), we used Cohen's kappa to assess concordance between clinical and SCAN diagnoses. Kappa values greater than 0.8 are considered almost perfect agreement; values between 0.4 and 0.7 are considered moderate to good agreement; and values below 0.4 are considered fair to poor (Fayers and MacHin, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Shear et al (2000) and Taggart et al (2006), we used Cohen's kappa to assess concordance between clinical and SCAN diagnoses. Kappa values greater than 0.8 are considered almost perfect agreement; values between 0.4 and 0.7 are considered moderate to good agreement; and values below 0.4 are considered fair to poor (Fayers and MacHin, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has variable but acceptable reliability and validity and is regarded as the "gold standard" for determining psychiatric diagnoses. [39][40][41] To ensure inter-rater reliability, all SCID interviews were audiotaped, and 15% of the interviews were reviewed for diagnostic accuracy.…”
Section: Scid-imentioning
confidence: 99%
“…Research on the SCID-I has shown the instrument to be valid and reliable among various samples, including a test-retest reliability of .61 for MDD over a 7-to 10-day interval (e.g., Shear et al, 2000;Zanarini et al, 2000). The SCID-I was used in the current study to assess current MDD for descriptive purposes.…”
Section: Instrumentsmentioning
confidence: 99%